Review of Chinese species of genus Phlogothamnus Ishihara (Hemiptera: Cicadellidae: Deltocephalinae) with description of a new species - Yao, Binbin; Zhang, Runzhi; Xing, Jichun (Zootaxa, 2022)
The Chinese leafhopper species of the genus Phlogothamnus Ishihara,1961 are reviewed, and a new species Phlogothamnus circinatus sp. nov., is described and illustrated from Guizhou Province, China. And the species Phlogothamnus fanjingshanensis Li, 2011 treated as Phlogotettix fanjingshanensis (Li, 2011) comb. nov.. A key is given to separate all species of the genus from China. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).